ТАРИЙХЫЙ ҚОСЫҚЛАРДА АТА ЖУРТЫ ТҮРКИСТАН ТЕМАСЫ - Қанаатов, Е.Е. (SCIENCE and SOCIETY, 2020)
The article notes that the Karakalpaks migrated to Turkistan along the Edil-Jayik rivers in the late 16th century. The people of Karakalpakstan have experienced many difficulties in their history. In the 13th century, the army of Genghis Khan conquered Khorezm. After that, most of the Karakalpaks living in the Turan lowland migrated to the Crimea, the Urals, and the Volga-Yaik. Unable to live there permanently, the Karakalpaks moved to Turkistan. The merciless attacks of the enemy do not allow him to stay here for long. By 1723, after the invasion of the Kalmyks, the Karakalpaks were divided into two parts. The upper Karakalpaks move to the Ferghana Valley, and the lower Karakalpaks move to the lower Syr Darya. The article analyzes historical songs that have arisen on the basis of such historical events.
Keywords: folklore; historical song; Turkestan period; Syrdarya; Upper Karakalpaks; Lower Karakalpaks